Preparation method suitable for sodium ion battery hard carbon negative electrode with high first effect and ultrahigh specific capacity

By combining carbon-containing materials with nitrogen-containing doping sources and compounding them with MXene, a high-first-effect and ultra-high specific capacity sodium ion battery hard carbon anode material was prepared, which solved the shortcomings of the first Coulomb efficiency and specific capacity improvement of the electrode energy density.

CN119650599AActive Publication Date: 2025-03-18YANGZHOU UNIV

Patent Information

Application Number
CN202411563044.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-18
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Sodium ion battery hard carbon anode material has disadvantages in the first improvement of Coulomb efficiency and specific capacity, which limits the commercial development of high-energy density sodium ion batteries.

Method used

A carbon-containing material is used as a hard carbon precursor, and nitrogen-doped hard carbon powder is prepared by adding a nitrogen-containing doping source for high temperature pyrolysis, and is compounded with MXene, and MXene composited sodium ion battery hard carbon anode material is obtained through electrostatic self-assembly.

Benefits of technology

It significantly improves the spatial and mass energy density of the electrode, improves the first charge and discharge efficiency and reversible specific capacity, enhances the electrochemical stability, and is suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650599A_ABST
    Figure CN119650599A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sodium ion battery hard carbon negative electrode with high first efficiency and ultrahigh specific capacity. Comprising the following steps: taking a carbon-containing material as a hard carbon precursor, and carrying out pre-oxidation treatment on the hard carbon precursor through a muffle furnace; and adding a nitrogen-containing doping source into the hard carbon precursor, putting the mixture into a vacuum tube furnace containing a protective atmosphere, calcining and pyrolyzing, and naturally cooling. The carbon-containing material is used as a precursor, the nitrogen-doped hard carbon powder is prepared through high-temperature pyrolysis by adding the nitrogen-containing doping source, and the nitrogen-doped hard carbon powder is compounded with MXene to obtain the self-supporting structure electrode material, so that the space and mass energy density of the electrode is greatly improved. MXene on the surface of the hard carbon anode material not only has excellent conductivity and electrochemical stability, but also can effectively prevent electrolyte from damaging the surface structure of the hard carbon, so that the first charge-discharge efficiency and reversible specific capacity of the hard carbon anode material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy technology, and in particular to a method for preparing a hard carbon negative electrode for a sodium ion battery with high initial efficiency and ultra-high specific capacity. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices and power batteries due to their high energy density, good cycle performance and environmental friendliness. However, the scarcity of lithium resources (crust abundance 0.0065%) makes it increasingly difficult to meet the needs of the rapidly developing energy storage market, and the production cost remains high. It is worth noting that sodium resources are abundant (crust abundance 2.75%) and widely distributed. Sodium-ion batteries have similar working principles to lithium-ion batteries and have better low-temperature performance, excellent rate performance, cycle stability and high safety. They are considered to be one of the energy storage systems with the greatest potential for large-scale application. The performance of sodium-ion batteries mainly depends on the selection of electrode materials, electrolytes, etc. In particular, in the negative electrode material system, hard carbon has the advantages of high capacity, long cycle stability and easy preparation, and is the most promising type of sodium negative electrode for industrial application. However, compared with the commercialized graphite negative electrode of lithium-ion batteries, hard carbon still faces the disadvantages of low first coulomb efficiency and difficulty in significantly improving specific capacity, which to a certain extent restricts the commercial development of high-energy-density sodium-ion batteries.

[0003] Patent CN1422235A discloses a method of preparing hard carbon materials by liquid phase dehydration, washing, drying and high temperature carbonization of resins in an autoclave. This method has complicated preparation process and is difficult to realize industrial production. Patent CN103311519A discloses a composite hard carbon material prepared by cross-linking polymerization reaction of asphalt, crushing, grading and high temperature carbonization. Although the preparation process is simplified, there are still problems such as low initial coulomb efficiency and limited capacity improvement. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a hard carbon negative electrode for a sodium ion battery with high initial efficiency and ultra-high specific capacity, so as to solve the technical problems raised in the background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] S1, using a carbon-containing material as a hard carbon precursor, heating the material to a preset heating temperature at a first preset heating rate through a muffle furnace, and heating the material to a preset heating time, to perform a pre-oxidation treatment on the hard carbon precursor;

[0007] S2, adding a nitrogen-containing doping source to the hard carbon precursor after the pre-oxidation treatment and placing it in a vacuum tube furnace containing a protective atmosphere for multi-step calcination and pyrolysis, and naturally cooling to obtain a nitrogen-doped hard carbon powder;

[0008] S3, using MXene material as a precursor for preparing a solution, and etching the MXene material by an acid etching method to prepare a MXene aqueous solution with a negatively charged surface;

[0009] S4, treating the nitrogen-doped hard carbon powder with a cationic surfactant solution to prepare an aqueous solution of nitrogen-doped hard carbon powder with a positively charged surface;

[0010] S5. Add the nitrogen-doped hard carbon powder aqueous solution with positive surface charge into the MXene aqueous solution with negative surface charge, perform probe ultrasonication for 5 to 10 minutes, perform electrostatic self-assembly, filter after the assembly is completed, and finally vacuum dry at 60°C to obtain the MXene composite hard carbon negative electrode material for sodium ion batteries.

[0011] Furthermore, the specific steps of step S2 are:

[0012] S21, adding a nitrogen-containing doping source to a hard carbon precursor, and placing the mixture in a vacuum tube furnace containing a protective atmosphere;

[0013] S22, heating to a first preset calcination temperature at a second preset heating rate, and calcining to a first preset calcination time;

[0014] S23, heating the mixture to a second preset calcination temperature at a third preset heating rate, calcining the mixture to a second preset calcination time, and then naturally cooling the mixture to room temperature to obtain nitrogen-doped hard carbon powder.

[0015] Furthermore, the ratio of the hard carbon precursor to the nitrogen-containing doping source is 9:1, the mass ratio of the MXene material to the nitrogen-doped hard carbon powder can be 1:0.05-20, the ratio of the MXene material to the acid is 1:6.57, and the ratio of the cationic surfactant solution to the nitrogen-doped hard carbon powder is 1:50.

[0016] Furthermore, the first preset heating rate in step S1 is preferably 1-5°C / min, the preset heating temperature is preferably 180-280°C, the heating time is preferably 0.1-10h, and the carbon-containing material can be biomass-based, phenolic resin-based, or asphalt-based.

[0017] Furthermore, the biomass base can be glucose, sucrose, starch, lignin, coconut shell, the phenolic resin base can be phenolic resin, epoxy resin, polyfurfuryl alcohol, and the asphalt base can be coal tar asphalt, petroleum asphalt, natural asphalt.

[0018] Furthermore, the protective atmosphere in step S2 is preferably nitrogen, argon or a mixture of the two, the protective atmosphere gas flow rate in the vacuum tube furnace is 0.1-0.5 L / min, and the nitrogen-containing doping source can be urea, NH4Cl, melamine, or m-aminophenol.

[0019] Furthermore, in the step S22, the second preset heating rate is preferably 0.5-10°C / min, the first preset calcination temperature is preferably 600-1600°C, and the first preset calcination time is preferably 0.1-10h; the third preset heating rate in the step S23 is preferably 0.5-10°C / min, the second preset calcination temperature is preferably 600-1600°C, and the second preset calcination time is preferably 0.1-10h.

[0020] Furthermore, the acid in the acid etching method in step S3 is preferably a mixture of LiF and HCL, wherein the mixing ratio of LiF and HCL is 1:6.57, the MXene material can be Ti3AlC2, Ti2AlC, and the MXene aqueous solution can be Ti3C2T x , Ti2CT x ,TiNbCT x ,Ti3CN x T x ,Ta4C3T x ,Nb2CT x ,V2CT x ,Nb4C3T x ,Mo2CT x ,(Nb 0.8 Ti 0.2 )4C3T x ,(Nb 0.8 Zr 0.2 )4C3T x ,Zr3C2T x and Hf3C2T x .

[0021] Furthermore, the cationic surfactant in step S4 is preferably hexadecyltrimethylammonium bromide (CTAB), octadecyl diester quaternary ammonium salt, hexadecanol polyoxyethylene ether dimethyl octyl ammonium chloride, the concentration of the cationic surfactant solution is preferably 0.1 to 20 mg / mL, and the treatment time of the active agent solution is preferably 0.2 to 20 h.

[0022] Furthermore, the electrostatic self-assembly time in step S5 is preferably 0.1 to 10 hours.

[0023] Beneficial effects:

[0024] 1. The present invention uses carbon-containing materials as hard carbon precursors to prepare nitrogen-doped hard carbon powder by adding nitrogen-containing doping sources and high-temperature pyrolysis, and obtains self-supporting structure electrode materials by compounding with MXene, avoiding the use of current collectors and greatly improving the space and mass energy density of the electrode. The MXene on its surface not only has excellent conductivity and electrochemical stability, but also can effectively block the damage of the electrolyte to the hard carbon surface structure. In particular, thanks to the appropriate interlayer spacing of MXene, the co-embedded solvent molecules in the carbon layer can be effectively screened, greatly improving the initial charge and discharge efficiency and reversible specific capacity of the hard carbon negative electrode material.

[0025] 2. The preparation process of the present invention is simple, free of toxic solvents, green and environmentally friendly, the preparation method has a high yield and low production cost, the product properties are stable, there is almost no difference between batches, the repeatability is good, it is suitable for large-scale preparation, and the hard carbon precursor has a wide source.

[0026] 3. The MXene used in the present invention is a two-dimensional material with excellent conductivity and electrochemical interface stability. In addition, it can effectively block the damage of the electrolyte to the surface structure of hard carbon. In particular, the appropriate interlayer spacing can effectively screen the co-embedding of solvent molecules in the carbon layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions implemented in the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope image of the electrode material Glu-1400 in Comparative Example 1 of the present invention;

[0029] Figure 2 This is a scanning electron microscope image of the electrode material NGlu-1400 in Comparative Example 2 of the present invention;

[0030] Figure 3 This is a scanning electron microscope image of the sodium ion battery hard carbon negative electrode material MNGlu-1400 which is compounded with MXene after the glucose precursor of the present invention is treated with a nitrogen-containing doping source;

[0031] Figure 4 This is an experimental data table of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0032] Figure 5 This is the first charge and discharge diagram after the hard carbon negative electrode materials of Example 1 and Comparative Examples 1 and 2 of the present invention are assembled into button-type batteries;

[0033] Figure 6This is a cycle performance diagram of button-type batteries assembled with hard carbon negative electrode materials of Example 1 and Comparative Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Please refer to Figure 1-Figure 6 The present invention provides a method for preparing a hard carbon negative electrode for a sodium ion battery with high initial efficiency and ultra-high specific capacity, and the specific steps are as follows:

[0036] Example 1

[0037] S1. Using glucose as a hard carbon precursor, heating the temperature to a preset heating temperature of 200° C. at a first preset heating rate of 2° C. / min in a muffle furnace, and heating to a preset heating time of 10 h, to pre-oxidize the hard carbon precursor.

[0038] S2. Add urea to the glucose precursor after pre-oxidation treatment and place it in a vacuum tube furnace containing argon gas for multi-step calcination and pyrolysis, and naturally cool it to obtain nitrogen-doped glucose-derived hard carbon powder; wherein the protective atmosphere gas flow rate in the vacuum tube furnace is 0.2L / min.

[0039] To further illustrate the implementation of step S2, the specific steps are as follows:

[0040] S21, adding 0.7 g urea to 6.3 g of glucose precursor, and placing the mixture in an argon vacuum tube furnace with a gas flow rate of 0.2 L / min;

[0041] S22, heating to 600°C at 5°C / min, and calcining for 2h;

[0042] S23, then raising the temperature to 1400° C. at a rate of 2° C. / min, and calcining for 0.5 hours, and then naturally cooling to room temperature to obtain nitrogen-doped glucose-derived hard carbon powder.

[0043] S3, 1g of Ti3AlC2 powder was used as a precursor for preparing the solution, and 20ml of LiF and HCl mixture was used to etch the Ti3AlC2 powder to prepare Ti3C2T with negative surface charge. x An aqueous solution, wherein the mixing ratio of LiF and HCl is 1:6.57;

[0044] S4, treating nitrogen-doped glucose-derived hard carbon powder with 10 μl of 5 mg / ml cationic surfactant CTAB to prepare an aqueous solution of nitrogen-doped glucose-derived hard carbon powder with a positive surface charge, wherein the concentration is 5 mg / ml and the CTAB treatment time is 2 h;

[0045] S5. Add the nitrogen-doped glucose-derived hard carbon powder aqueous solution into 8.2 ml of Ti3C2T x In the aqueous solution, the probe was ultrasonicated for 5 to 10 minutes, and electrostatic self-assembly was performed for 10 minutes. After the assembly was completed, it was filtered and finally vacuum dried at 60°C to obtain a MXene-composite sodium-ion battery hard carbon negative electrode material, which was named MNGlu-1400.

[0046] Embodiments 2-4 are substantially the same as Embodiment 1, and the specific differences are shown in the following table:

[0047]

[0048] Please refer to Figure 4-Figure 6 The present invention has high initial coulombic efficiency, reversible capacity and excellent cycle performance. Now, a glucose precursor is used as a hard carbon precursor, and the following comparative examples and experimental data are used to illustrate:

[0049] Comparative Example 1 is a hard carbon powder made from a glucose precursor without adding a nitrogen-containing doping source:

[0050] 6.3 g of glucose precursor was placed in a vacuum tube furnace containing an argon protective atmosphere with a protective atmosphere gas flow rate of 0.2 L / min. The temperature was increased to 600°C at a heating rate of 5°C / min and calcined for 2 hours. The temperature was then increased to 1400°C at a heating rate of 2°C / min and calcined for 0.5 hours. After naturally cooling to room temperature, a glucose-derived hard carbon powder was obtained, which was named Glu-1400.

[0051] Comparative Example 2 is a hard carbon powder prepared by adding a nitrogen-containing doping source to a glucose precursor:

[0052] 6.3 g of glucose precursor was added to 0.7 g of urea and placed in a vacuum tube furnace containing an argon protective atmosphere. The protective atmosphere gas flow rate in the vacuum tube furnace was 0.2 L / min. The temperature was increased to 600°C at a heating rate of 5°C / min and calcined for 2 hours. Then the temperature was increased to 1400°C at a heating rate of 2°C / min and calcined for 0.5 hours. After naturally cooling to room temperature, nitrogen-doped glucose-derived hard carbon powder was obtained, which was named NGlu-1400.

[0053] Please refer to Figure 1-Figure 2 , Figure 1 This is a scanning electron microscope image of the electrode material Glu-1400 in Comparative Example 1. Figure 2 The scanning electron microscope image of the electrode material NGlu-1400 in Comparative Example 2 is shown in Figure 1. The electrode material Glu-1400 obtained in Comparative Example 1 and the electrode material NGlu-1400 obtained in Comparative Example 2 are respectively used as button battery negative electrode materials to assemble button batteries. The first charge and discharge test was carried out at a current density of 0.1C and a voltage window of 0-3V, and the cycle performance was tested at a current density of 1C discharge and 5C charge. The test results are shown in Figure 1. Figure 4 As shown, the present invention adopts a method of preparing negative electrode materials by adding a nitrogen-containing doping source to a hard carbon precursor and then pyrolyzing it at high temperature, which has high initial coulombic efficiency, reversible capacity and excellent cycle performance.

[0054] Figure 3 The figure is a scanning electron microscope image of a MXene-composite hard carbon negative electrode material (MNGlu-1400) for a sodium ion battery. The electrode material (MNGlu-1400) obtained in Example 1 is used as a button battery negative electrode material to assemble a button battery. The first charge and discharge test is carried out at a current density of 0.1C and a voltage window of 0-3V, and the cycle performance is tested at a current density of 1C discharge and 5C charge. The MXene-composite hard carbon negative electrode material for a sodium ion battery prepared by the present invention has a high initial coulombic efficiency, reversible capacity and excellent cycle performance, as shown in FIG. Figure 4 As shown, it exhibits an initial coulombic efficiency of 94.33% and an ultra-high specific capacity of 471.5mAh / g. Moreover, the capacity can still be maintained at 97.8% after 200 cycles at a discharge / charge current density of 1C / 5C. Please refer to Figure 5 and Figure 6 The MXene composite hard carbon negative electrode material for sodium ion batteries obtained by the preparation method provided by the present invention has high initial coulombic efficiency, reversible capacity and excellent cycle performance, which solves the core scientific problems of low initial charge and discharge efficiency and low capacity of hard carbon negative electrode materials for sodium ion batteries, and is expected to lay a solid foundation for the widespread application of sodium ion batteries.

[0055] The present invention discloses a method for preparing a hard carbon negative electrode for a sodium ion battery with high initial efficiency and ultra-high specific capacity. The MXene used is a two-dimensional material with excellent conductivity and electrochemical interface stability. In addition, it can effectively block the electrolyte from damaging the hard carbon surface structure. In particular, the appropriate interlayer spacing can effectively screen the co-embedding of solvent molecules in the carbon layer. The present invention uses a carbon-containing material as a hard carbon precursor, adds a nitrogen-containing doping source, and pyrolyzes it at high temperature to prepare nitrogen-doped hard carbon powder, and then composites it with MXene to obtain a three-dimensional MXene coating layer structure, which can effectively alleviate the Na +The volume expansion caused by insertion greatly improves the cycle stability of the electrode. This structure is a self-supporting electrode material, which avoids the use of a current collector and greatly improves the spatial and mass energy density of the electrode. The MXene on its surface not only has excellent conductivity and electrochemical stability, but also can effectively block the damage of the electrolyte to the hard carbon surface structure. In particular, thanks to the appropriate interlayer spacing of MXene, it can effectively screen the co-embedded solvent molecules in the carbon layer, greatly improving the initial charge and discharge efficiency and reversible specific capacity of the hard carbon negative electrode material.

[0056] Therefore, the MXene-composite hard carbon negative electrode material for sodium ion batteries can effectively improve the electrochemical stability and sodium storage capacity of the electrode, while saving the use of the negative electrode current collector, which is extremely beneficial to the design of high space and high quality energy density batteries. The preparation process of the present invention is simple, non-toxic solvent, green and environmentally friendly, the preparation method has high yield and low production cost, stable product properties, almost no difference between batches, good repeatability, suitable for large-scale preparation, and a wide range of hard carbon precursor sources.

[0057] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0058] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a hard carbon negative electrode for a sodium ion battery with high initial efficiency and ultra-high specific capacity, characterized in that: The following steps are involved: S1, using a carbon-containing material as a hard carbon precursor, heating the material to a preset heating temperature at a first preset heating rate through a muffle furnace, and heating the material to a preset heating time, to perform a pre-oxidation treatment on the hard carbon precursor; S2, adding a nitrogen-containing doping source to the hard carbon precursor after the pre-oxidation treatment and placing it in a vacuum tube furnace containing a protective atmosphere for multi-step calcination and pyrolysis, and naturally cooling to obtain a nitrogen-doped hard carbon powder; S3, using MXene material as a precursor for preparing a solution, and etching the MXene material by an acid etching method to prepare a MXene aqueous solution with a negatively charged surface; S4, treating the nitrogen-doped hard carbon powder with a cationic surfactant solution to prepare an aqueous solution of nitrogen-doped hard carbon powder with a positively charged surface; S5. Add the nitrogen-doped hard carbon powder aqueous solution with positive surface charge into the MXene aqueous solution with negative surface charge, perform probe ultrasonication for 5 to 10 minutes, perform electrostatic self-assembly, filter after the assembly is completed, and finally vacuum dry at 60°C to obtain the MXene composite hard carbon negative electrode material for sodium ion batteries.

2. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The specific steps of step S2 are: S21, adding a nitrogen-containing doping source to a hard carbon precursor, and placing the mixture in a vacuum tube furnace containing a protective atmosphere; S22, heating to a first preset calcination temperature at a second preset heating rate, and calcining to a first preset calcination time; S23, heating the mixture to a second preset calcination temperature at a third preset heating rate, calcining the mixture to a second preset calcination time, and then naturally cooling the mixture to room temperature to obtain nitrogen-doped hard carbon powder.

3. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The ratio of the hard carbon precursor to the nitrogen-containing doping source is 9:1, the mass ratio of the MXene material to the nitrogen-doped hard carbon powder can be 1:0.05-20, the ratio of the MXene material to the acid is 1:6.57, and the ratio of the cationic surfactant solution to the nitrogen-doped hard carbon powder is 1:

50.

4. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The first preset heating rate in step S1 is preferably 1-5°C / min, the preset heating temperature is preferably 180-280°C, the heating time is preferably 0.1-10h, and the carbon-containing material can be biomass-based, phenolic resin-based, or asphalt-based.

5. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 4, characterized in that: The biomass base can be glucose, sucrose, starch, lignin, coconut shell, the phenolic resin base can be phenolic resin, epoxy resin, polyfurfuryl alcohol, and the asphalt base can be coal tar asphalt, petroleum asphalt, natural asphalt.

6. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The protective atmosphere in step S2 is preferably nitrogen, argon or a mixture of the two. The protective atmosphere gas flow rate in the vacuum tube furnace is 0.1-0.5 L / min. The nitrogen-containing doping source can be urea, NH4Cl, melamine, or m-aminophenol.

7. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 2, characterized in that: In the step S22, the second preset heating rate is preferably 0.5-10°C / min, the first preset calcination temperature is preferably 600-1600°C, and the first preset calcination time is preferably 0.1-10h; The third preset heating rate in step S23 is preferably 0.5-10° C. / min, the second preset calcination temperature is preferably 600-1600° C., and the second preset calcination time is preferably 0.1-10 h.

8. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The acid in the acid etching method in step S3 is preferably a mixture of LiF and HCL, wherein the mixing ratio of LiF and HCL is 1:6.57, the MXene material can be Ti3AlC2, Ti2AlC, and the MXene aqueous solution can be Ti3C2T x , Ti2CT x ,TiNbCT x ,Ti3CN x T x ,Ta4C3T x ,Nb2CT x ,V2CT x ,Nb4C3T x ,Mo2CT x ,(Nb 0.8 Ti 0.2 )4C3T x ,(Nb 0.8 Zr 0.2 )4C3T x ,Zr3C2T x and Hf3C2T x .

9. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The cationic surfactant in step S4 is preferably hexadecyltrimethylammonium bromide (CTAB), octadecyl diester quaternary ammonium salt, hexadecyl polyoxyethylene ether dimethyl octyl ammonium chloride, the concentration of the cationic surfactant solution is preferably 0.1-20 mg / mL, and the treatment time of the active agent solution is preferably 0.2-20 h.

10. The method for preparing a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The electrostatic self-assembly time in step S5 is preferably 0.1 to 10 hours.

Citation Information

Patent Citations

  • Composite hard carbon negative electrode material, and preparation method and application thereof

    CN103311519A

  • Pyrolyzed hard carbon material, preparation and its applications

    CN1422235A

  • Preparation method and application of nitrogen-doped MXene battery anode material

    CN106025200A

  • Composite material, preparation method and application thereof, electrode and lithium ion battery

    CN110752364A

  • Nitrogen-doped hard carbon material and preparation method and application thereof

    CN113493195A

Cited By

  • Hard carbon negative electrode material and preparation method and application thereof

    CN120398033A